Skin cancer detection and classification using multiple optimized deep convolutional neural network - Sakir, Adnan; Chowdhury, Mustakim Anwar; Rahman, Maksura; Mostafiz, K. M Shefat (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.